Evaluating the impact of knowledge-based CAD on aerostructural design - Bates, J. P. (Cranfield University, 1998)
Knowledge based enhancements to CAD systems are currently being offered as a means of furthering designer performance in the product development process. A considerable body of research has already taken place to define how such systems work and further options are currently being explored to build on achievements to date. However, the uptake of such systems in industrial practice is not widespread and assessment of such systems are not well documented in the literature. The present work first reviews current CAD practice as 'computer-aided drafting' and highlights the limitations and difficulties associated with the continued exclusive use of such systems in design. The need for proper uptake of knowledge-based CAD systems is then described, demonstrated and assessed. This thesis considers some of the difficulties associated with introducing knowledge based CAD systems onto the critical path of engineering programmes and sets out to evaluate the performance of one such system in the context of a live aircraft development project. The commercially available /knowledge-based engineering ÄUKBE) system ICAD from Concentra Ltd is selected for assessment in the context of aero structural design. A case study demonstrator is developed to automate the solid modelling of light alloy fuselage frame sectors and applied in practical design trials to determine its performance against well understood conventional CAD system expectations. The major contribution of the thesis is in assessing the impact on working practice of introducing KBE systems into the aircraft design process. The business benefits of using KBE systems in an aerospace engineering programme are quantified. Some ideas for the extended functionality of such systems to achieve a greater level of generic applicability are presented and implications of use of such systems discussed. Finally, recommendations for the extended deployment of KBE systems to achieve strategic market advantage in an aerospace context are given.